(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Forced bioconversion of solid organic wastes as technology for Latvia conditions is presented. Every inhabitant produces 200 300kg solid wastes, about 0,6 mind per year in Latvia. Different technologies are used for utilisation of these wastes. The most popular are: landfilling, sorting and recycling, incineration, composting and anaerobic digestion for organic wastes. As new technology? in Latvia is forced bioconversion of municipal solid organic wastes. Approximately 250000 tons solid wastes per year are coming to landfill Getlini. 24% from them are usable for anaerobic digestion. Regulating of temperature and moisture content in wastes gives possibility to optimise process of bioconversion. Forced anaerobic bioconversion proceeds 4 -7 times faster as normal bioconversion in landfill. For this technology is necessary less investment for incineraton anaerobic digestion in bioreactors and composting in tunnels or halls. It is preferable for smaller landfills in Latvia too. For big landfill, where has sorting, the best solution: approximately 30% recycling, 25% wet organic for forced bioconversion, 45% for incineration.